Motivation, Pleasure and a Playful Methodology in Language Learning - Caon, Fabio (Educazione Linguistica Language Education, 2020)
Motivation is a fundamental motor for meaningful learning, or that which is stable and lasting in our memory. It can be defined as a motor because it etymologically ‘moves’ us toward a goal, while also determining the intensity and duration of the movement. This aspect is key as it reveals the didactic necessity to continuously sustain motivation. This article analyses these elements to present the playful methodology as one of the possible solutions to help students develop a passion for learning a new language.